Ethnolinguistic Concerns in the Philippines - Malicsi, Jonathan (The Archive, 2025)
Of the various interdisciplinary studies of language that have crystallized into fields of specialization, ethnolinguistics, or anthropological linguistics, or linguistic anthropology, has not received as much attention here in the Philippines from either linguists or other social scientists. Understandably, sociolinguistics and psycholinguistics have recently been in the forefront of much talk about the language situation in our country (much of it rather heated and tending to fly off) because of controversies related to our fragmented language policies. But because its immediate relevance to such language policies has not been widely apparent even to linguists and language teachers, ethnolinguistics has remained largely identified with the study of the cultures of our less populous groups.